Expression Analysis of Same-Patient Metachronous and Synchronous Upper Tract and Bladder Urothelial Carcinoma. Issue 3 (21st September 2021) - Petros, Firas G.; Choi, Woonyoung; Qi, Yuan; Moss, Tyler; Li, Roger; Su, Xiaoping; Guo, Charles C.; Czerniak, Bogdan; Dinney, Colin; McConkey, David J.; Matin, Surena F.
Abstract : Purpose: We compared upper tract urothelial carcinoma (UTUC) and bladder urothelial carcinoma (BUC) in same-patient metachronous UTUC and synchronous UTUC and BUC using next-generation sequencing. Materials and Methods: Consecutive untreated same-patient samples of UTUC and BUC were macrodissected from unstained formalin-fixed, paraffin-embedded slides after quality control. Samples were divided into 4 groups: 1) UTUC-metachronous BUC, 2) BUC-metachronous UTUC, 3) synchronous UTUC-BUC, 4) UTUC without BUC. Exclusions were inadequate clinical data or histological tumor purity <30%. Whole transcriptome RNA sequencing was performed. After quality assessment, gene expression clusters using unsupervised hierarchical consensus clustering and correlation with pertinent clinicopathologic variables, a prior RNASeq data set and other published data were performed. Results: RNAseq was performed on 95 samples (UTUC=61, BUC=34) from 40 untreated patients. Unsupervised consensus clustering segregated the tumors into 2 clusters that were enriched with BASE47 basal-like or luminal-like gene expression. Almost two-thirds (61.9%) of Group 2 tumors were basal-like, while the majority of Groups 1, 3, 4 (80.6%, 70.0% and 69.6%, respectively) were luminal-like (p=0.017). Further analyses revealed that the differences in basal-like and luminal-like gene expression were associated with differential fibroblast and immune cell gene expression signatures. In all, 87.5% of metachronous tumors maintained subtype membership. Conclusions: Gene expression analysis of same-patient metachronous UTUC-BUC suggests that the majority of mUTUC developing after BUC appear more basal-like, while synchronous and initial UTUC tumors appear luminal-like. Metachronous tumors largely maintain molecular subtype membership of the initial tumor regardless of chronologic development or anatomical origin.